2016
DOI: 10.4103/0971-5916.193293
|View full text |Cite
|
Sign up to set email alerts
|

Distribution trends & antibiogram pattern of Salmonella enterica serovar Newport in India

Abstract: Background & objectives:Salmonellosis is a major public health concern worldwide. Besides typhoidal salmonellae, infections due to non-typhoidal serovars of Salmonella are also associated with high morbidity and mortality leading to huge economic losses. Among non-typhoidal serovars, Salmonella Newport has been reported as a major cause of foodborne infections resulting in outbreaks due to consumption of contaminated food items. Little data related to this serovar are available from India leading to the scarci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 18 publications
1
5
0
Order By: Relevance
“…Patients with MDRAB infections had a high incidence of polymicrobial infections (88%) and chronic comorbidities (66%); these were likely the confounders contributing to increased mortality. Our finding matches many studies from different parts of the world; they found several folds increase in mortality rate in MDRAB infected patients than in those infected with susceptible phenotypes, as well as increased hospital and intensive care unit length of stay [ 34 , 35 , 36 ].…”
Section: Discussionsupporting
confidence: 91%
“…Patients with MDRAB infections had a high incidence of polymicrobial infections (88%) and chronic comorbidities (66%); these were likely the confounders contributing to increased mortality. Our finding matches many studies from different parts of the world; they found several folds increase in mortality rate in MDRAB infected patients than in those infected with susceptible phenotypes, as well as increased hospital and intensive care unit length of stay [ 34 , 35 , 36 ].…”
Section: Discussionsupporting
confidence: 91%
“…These data are in agreement with findings in the literature, since strains isolated from fish have been showing resistance to this first-generation cephalosporin 32 , 33 . In addition, cefoxitin- and cefuroxime-resistant bacteria have also been isolated from food 34 , 35 .…”
Section: Discussionmentioning
confidence: 99%
“…Another study from India also recorded moderate resistance in Salmonella Newport isolated from poultry and animal origin foods. However, a high degree of sensitivity was observed against ciprofloxacin, chloramphenicol and cefuroxime (Kumar et al, 2016). Isolates of our study were mostly sensitive to cephalosporins but they have shown resistance to colistin, tetracycline and certain penicillin group of antimicrobials.…”
Section: Antibiogrammentioning
confidence: 49%